The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.17221/209/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

NaCl salinity-induced changes in water status, ion contents and photosynthetic properties of Shepherdia argentea (Pursh) Nutt. seedlings

Abstract: Two-year old seedlings of Silver buffaloberry (Shepherdia argentea (Pursh) Nutt.) were exposed to NaCl salinity (0, 200, 400 and 600 mmol/l) for 30 days. Leaf water potential (Ψ w ), chlorophyll contents (Chl a, b, and a + b) and K + content decreased with an increase in salinity. Relative water content (RWC) declined significantly with 400 and 600 mmol/l NaCl. However, salinity induced an excessive accumulation of Na + in the leaves of plants. Light responses of photosynthesis showed that net photosynthetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 22 publications
5
41
1
1
Order By: Relevance
“…Differences (p < 0.05) were obtained for Chl-a and total chlorophylls, values decreasing when soil salinity content increases, but no differences in the Chl-b content were found. Previous studies also reported that Chl-b was less sensitive to salt stress than Chl-a (Naumann et al, 2008;Qin et al, 2010). However, no correlation was found between chlorophylls and the NDVI indices used in this work thus indicating that levels of chlorophyll were not the only parameter affecting NDVI indices.…”
Section: Resultscontrasting
confidence: 73%
“…Differences (p < 0.05) were obtained for Chl-a and total chlorophylls, values decreasing when soil salinity content increases, but no differences in the Chl-b content were found. Previous studies also reported that Chl-b was less sensitive to salt stress than Chl-a (Naumann et al, 2008;Qin et al, 2010). However, no correlation was found between chlorophylls and the NDVI indices used in this work thus indicating that levels of chlorophyll were not the only parameter affecting NDVI indices.…”
Section: Resultscontrasting
confidence: 73%
“…When salt stress becomes severe and CO 2 assimilation is significantly disturbed, the role of nonstomatal factors in the limitation of photosynthesis usually becomes more pronounced (Brugnoli and Lauteri 1991;Qin et al 2010). As can be seen in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Water status is a major factor affecting plant growth and development. A decrease of the leaf relative water content under saline conditions has been observed frequently (Qin et al, 2010;Aroca et al, 2012). The decrease of water uptake under salt stress conditions could be a strategy to diminish the water flow from the roots to the soil while the soil osmotic potential is lower than that of the roots.…”
Section: Leaf Relative Water Content Capacitymentioning
confidence: 99%